2009
DOI: 10.1021/jo902572y
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Regioselectivity of Diels−Alder Reactions for the Synthesis of Bisanthraquinone Antibiotic BE-43472B

Abstract: The regioselectivities of several Diels-Alder reactions utilized en route to bisanthraquinone antibiotic BE-43472B are examined using density functional theory calculations. These reactions involve highly substituted dienes and juglone dienophiles, and there is an opposite regiochemical outcome for Diels-Alder reactions with β-aryl substituted juglones when compared to reactions of unsubstituted juglone. In this article, the effect of an aromatic conjugating group bonded to juglone is explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…On the basis of the above results as well as other reports, a plausible reaction mechanism is depicted in Scheme . According to the dual activation model, the two substrates involved in the reaction are activated simultaneously by the bifunctional catalyst.…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…On the basis of the above results as well as other reports, a plausible reaction mechanism is depicted in Scheme . According to the dual activation model, the two substrates involved in the reaction are activated simultaneously by the bifunctional catalyst.…”
Section: Methodssupporting
confidence: 74%
“…Relatively few mechanistic studies on quinones centered [4+2] cycloaddition have been conducted, but a concerted mechanism rather than a stepwise mechanism has been often suggested. However, based on a recent theoretical study, a stepwise ionic mechanism has been proposed .…”
Section: Methodsmentioning
confidence: 99%
“…We provide the whole potential energy profile of the tandem cycloaddition process in Figure and various conformers of species with small differences in energy in Figures S1–S4 (Supporting Information). The general mechanism shows that the first step of the cascade reaction corresponding to the D–A cycloaddition proceeds via the transition state TS1 with an activation free energy of 27.1 kcal/mol in a concerted but significantly asynchronous fashion, and both the diene and dienophile appear to be symmetrical. , The formation of the D–A adduct 3 is exergonic by 4.8 kcal/mol. The subsequent step is intramolecular [2 + 2 + 2] cycloaddition with an activation free energy of 29.9 kcal/mol in water (30.0 kcal/mol in MeCN).…”
Section: Resultsmentioning
confidence: 99%
“…In another synthetically motivated study, Nicolaou, Houk and co-workers examined the Diels-Alder reactions of highly substituted dienes with juglone (5-hydroxy-1,4-naphthalenedione) dienophiles (Scheme 5). 7 Such a cycloaddition served as a key step in a recent total synthesis of bisanthraquinone antibiotic BE-43472B by Nicolaou. The regioselectivity of this reaction was of interest, since prior studies showed that typically, when juglones are dienophiles, the more nucleophilic diene terminus will attack C2 of the juglone (Scheme 5).…”
Section: Cycloaddition Reactions [2+2] Reactionsmentioning
confidence: 99%